Second infection with a different hepatitis C virus genotype in a intravenous drug user during interferon therapy. Issue 6 (1st June 2003) - Asselah, T; Vidaud, D; Doloy, A; Boyer, N; Martinot, M; Vidaud, M; Valla, D; Marcellin, P
Abstract : The prevalence of antibodies against hepatitis C virus (anti-HCV) among intravenous drug users (IVDU) has consistently been very high. Cross challenge studies in chimpanzees provide evidence that reinfection with different HCV strains may occur. In humans, reinfection with different HCV strains has been reported in multitransfused haemophiliacs and recently in IVDU but no case has been reported while on interferon (IFN) therapy. We report on a 22 year old woman who was treated with IFN alpha for HCV genotype 3a chronic infection. At six months, HCV RNA was undetectable by reverse transcription-polymerase chain reaction. In October 1997, while still on IFN, she developed an acute hepatitis after an intravenous drug injection and HCV genotype 1a infection was identified using genotyping and sequencing methods. IFN therapy was continued until August 1998, and in January 1999 HCV-RNA was not detectable. Our case indicates that the previous HCV infection might have prevented development of chronicity. An alternative explanation is that IFN, while not preventing acute hepatitis C, may prevent chronicity. The risk of multiple infection in IVDU underlines the need for preventive strategies.